An Easy and Efficient Method to Functionalize Titanium Dioxide Nanoparticles with Maleic Anhydride - Del Castillo, Pável C. Hernández; Manuel, Saúl Robles; Ruiz, Facundo (Scientific Research, 2014)
In this work, titanium dioxide (TiO2) nanoparticles were functionalized with maleic anhydride (MA), using a non-polar (toluene) and polar protic (ethanol) solvents. The concentrations of MA in the reaction were varied to obtain the desired degree of functionalization. The samples were characterized with Fourier Transform Infrared Spectroscopy (FTIR), Diffuse Reflectance UV-Vis Spectroscopy (DRS), Thermal Analysis (TGA-DTA) and Nitrogen Adsorption (BET). The physical adsorption of organic molecules was eliminated by washing a number of times in water. Chemical stability between solid-organic phases was confirmed by TOC and thermal analysis. FT-IR and DRS results clearly show the chemical adsorption of MA on the TiO2. The UV-Vis spectroscopy is claimed to be a suitable technique to determine the achievement of TiO2 functionalization. Two different adsorptions geometries of MA were proposed. The presence of MA on the surface TiO2 increases the band gap. These results imply that TiO2 can be excited with less energy and increase the absorption of light in the visible region. The effectiveness of the functionalized nanoparticles to interact with organic materials is currently being studied with the intention of applying them in the energy and environmental sanitation fields.
Keywords: TiO2 Nanoparticles; Functionalization; Maleic Anhydride; Sensitization; Adsorption on Solid